IMPLEMENTASI ZACHMAN FRAMEWORK UNTUK PEMODELAN DAN PERANCANGAN SISTEM E-COMMERCE PADA SEKTOR PERDAGANGAN IKM - Siti Eka Chotimah; Sri Handayaningsih (Telematika, 2016)
Trade area is an area that is in Disperindagkop DIY. In performing the task in terms of facilitating, coaching and supervision of trading activities are still experiencing difficulties in getting data such as turnover and the products produced and sold by the merchant SMEs, the number of traders SMEs. Office http://jogjaplaza.com already have a website, which is used specifically to market the products of SMEs has not reached to the industry. Based on this problem, it needs to make a model and system design appropriate e-commerce in the hope can be used as a reference when establishing the e-commerce.Tahapan used in the modeling and design of e-commerce systems Disperindagkop domestic trade field include: ( 1) data collection with library research techniques, interviews and observation. (2) analysis of current conditions and expected (3) Analysis of Gap and (4) development of modeling and designing systems with methods Zachman framework and models of linear sequential process. (5) The test document using analytical testing and usability testing. The research resulted in a model and e-commerce system design that can be used as a reference in the development of e-commerce system based on the results of testing with a test value for 100% testing analysis and for testing usability testing to the respondent purchaser merchant value IKM value 3.3